Chemosensory Contributions of E-Cigarette Additives on Nicotine Use - Johnson, Natalie L.; Patten, Theresa; Ma, Minghong; De Biasi, Mariella; Wesson, Daniel W. (Frontiers in Neuroscience, 2022)
While rates of smoking combustible cigarettes in the United States have trended down in recent years, use of electronic cigarettes (e-cigarettes) has dramatically increased, especially among adolescents. The vast majority of e-cigarette users consume “flavored” products that contain a variety of chemosensory-rich additives, and recent literature suggests that these additives have led to the current “teen vaping epidemic.” This review, covering research from both human and rodent models, provides a comprehensive overview of the sensory implications of e-cigarette additives and what is currently known about their impact on nicotine use. In doing so, we specifically address the oronasal sensory contributions of e-cigarette additives. Finally, we summarize the existing gaps in the field and highlight future directions needed to better understand the powerful influence of these additives on nicotine use.